Short-term of clinical safety and efficiency of CO2 laserassisted sclerectomy surgery (CLASS) - YEZi; WANGDajiang; LIZhaohui (眼科学报; 卷 31, 编号 4 (December 2016): 《眼科学报》, 2016)
Objective: To evaluate the short-term of clinical safety and efficiency of CO 2 laser-assisted sclerectomy surgery (CLASS) in patient with open-angle glaucoma and complicated glaucoma. Methods: Our study involved 46 eyes of 46 patients with glaucoma that underwent CLASS and trabeculectomy respectively by the same surgeon (Zhaohui Li) from May 2015 to January 2016 at the PLA General Hospital. Intraocular pressure and complications 1 week, 1 month and 3 months after operation was observed separately. Results: The intraocular pressure (IOP) 1 week, 1 month and 3 months after surgery decreased obviously (P=0.000). Compared to the trabeculectomy group 1 week, 1 month and 3 months after surgery, IOP of CLASS group was lower. But there was no statistically significant between these two groups (P>0.05). There was no complication occurred in CLASS group. Early postoperative complications occurred in trabeculectomy group included shallow anterior chamber and choroidal detachment, and they were all successfully resolved by pharmacotherapy. Conclusion: CLASS operation could reduce intraocular pressure effectively and decrease the incidence of complications, such as postoperative shallow anterior chamber in patients with glaucoma. However, its long-term effect and complications need to be further studied.